Long-term performance evaluation of down-flow hanging sponge reactor regarding nitrification in a full-scale experiment in India. (March 2016) - Onodera, Takashi; Okubo, Tsutomu; Uemura, Shigeki; Yamaguchi, Takashi; Ohashi, Akiyoshi; Harada, Hideki
Graphical abstract: Highlights: First full-scale DHS reactor was operated at 1.5-h HRT for over 1800 days in India. Removal efficiency of the DHS reactor was 79% for NH4 -N and 65% for TN. The DHS exhibited high DO, sludge concentration, and nitrification activity. A full-scale DHS is practically applicable to developing countries. Abstract: The first full-scale down-flow hanging sponge (DHS) reactor applied to post-treatment of effluent from an upflow anaerobic sludge blanket (UASB) reactor for the treatment of municipal sewage was evaluated, with emphasis on nitrification. The full-scale DHS reactor was successfully operated at a hydraulic retention time of 1.5 h for over 1800 days in India. The DHS reactor produced effluent with 6 mg L −1 ammonium nitrogen, corresponding to 79% removal efficiency. The total nitrogen removal by the DHS reactor was 65%. The high process performance of the DHS reactor was supported by its distinctive characteristics of (1) high dissolved oxygen of 5.4 mg L −1 in the DHS effluent without forced ventilation, (2) dense retained sludge in the range of 23–46 gVSS Lsponge −1, and (3) adequate sludge activity of 52 mgN gVSS −1 day −1 for nitrification. The full-scale experiment has proven that the DHS reactor has practical applicability to developing countries.